Neonatal NR3C1 Methylation and Social-Emotional Development at 6 and 18 Months of Age - Folger, Alonzo T.; Ding, Lili; Ji, Hong; Yolton, Kimberly; Ammerman, Robert T.; Van Ginkel, Judith B.; Bowers, Katherine (Frontiers in Behavioral Neuroscience, 2019)
The variation in childhood social-emotional development within at-risk populations may be attributed in part to epigenetic mechanisms such as DNA methylation (DNAm) that respond to environmental stressors. These mechanisms may partially underlie the degree of vulnerability (and resilience) to negative social-emotional development within adverse psychosocial environments. Extensive research supports an association between maternal adversity and offspring DNAm of the NR3C1 gene, which encodes the glucocorticoid receptor. A gap in knowledge remains regarding the relationship between NR3C1 DNAm, measured in neonatal (1-month of age) buccal cells, and subsequent social-emotional development during infancy and early childhood. We conducted a longitudinal cohort study of n=53 mother-child dyads (n=30 with developmental outcomes formed the basis of current study) who were enrolled in a home visiting program. Higher mean DNAm of the NR3C1 exon 1F promoter was significantly associated with lower 6-month ASQ:SE scores—more positive infant social-emotional functioning. A similar trend was observed at 18-months of age in a smaller sample (n=12). The findings of this pilot study indicate that in a diverse and disadvantaged population, the level of neonatal NR3C1 DNAm is related to later social-emotional development. Limitations and implications for future research are discussed.